Kiprah Bisnis Pengusaha Santri dan Minimalitas Dukungan Pemrintah : Stdi Tentang Dinamika Ekonomi Santri Penganut Tarekt di Mlangi - Supraja, Muhamad (Magister Administrasi Publik (MAP) FISIPOL Universitas Gadjah Mada, 2010)
This article discusses the relationship between religion and economic activity, which special reference to businessmen who are adherents to Tarekat Qodiriyah Naqsabandiyah in Mlangi. Study findings show that businessmen who are adherents of tarekat teachings are generally successful in conduction their economic activities. Equiiped with such qualities and values, devotees of Tarekat Qodiriyah Naqsabandiyah are able to achieve success in creating markets, networks, and independent businesses. Nonetheless, the success they achieve is constrained by the existence of a market economy, which is the prevailing economic model in Indonesia in post Independence Indonesia. Thus it is surprising that unless advocacy for state assistance is made, businessmen in general in small scale businesses in particular will find it difficult to survive under the current economic model.